STUDENTS` LEARNING STRATEGIES IN ENGLISH COMMUNICATION AT IKIP MATARAM - Agus Salim; Tawali Terasne (STKIP PGRI Jombang, 2016)
This study is aimed at finding out the student`s learning strategies in English communication. Due to the learning strategies, researcher applied qualitative method. In collecting data the researcher used three procedures, interviewing, recording, and noting. Then data was analyzed in three ways, data reduction, data displayed, and conclusion. The subject consists of 40 students from the fifth semester. Finally the researcher found out that the strategies that the students used in learning communication was good. It means that the strategies can help them to improve the abilities in doing communication by English. It can be seen at finding of this study. The students `communication ability improve together with the process of teaching and learning in the classroom. There some strategies that they used: confirmation check, comprehension check, clarification check, and self-repetition. Through these strategies their mistake and also self-confident in expressing their ideas is better than before.